Implementation of Mind Mapping Learning Model to Improve English Learning Outcomes in Simple Descriptive Texts - Junaedy, Junaedy (Universitas Muhammadiyah Jember, 2018)
Writing is a linguistic activity that plays an important role in the dynamics ofhuman civilization. Through writing activities, people can also benefit for theirdevelopment. Unfortunately, English lessons at Ambulu 2 Junior High Schoolshowed indications of a decline. This is a classroom action research that aimedto find out how the implementation of mind mapping learning models canimprove English achievement of the seventh grade students of Class VII-C atSMPN 2 Ambulu. The results showed that learning with the Mind Mappingmodel had a positive impact in improving student learning outcomes whichwas marked by an increase in student’s achievement in each cycle, that is cycleI (61.76%), cycle II (76.47%), cycle III ( 94.12%). Likewise, the application ofthe Mind Mapping model can improve student learning activities as indicatedby the score of observations showing an increase in the percentage of studentactivity, that is cycle I (23.53%), cycle II (73.53%) and cycle III (91.18). This means that the mind mapping learning model is good to be applied in teaching andlearning activities in English materials for Preparing Simple Descriptive Texts.